Recanalization of coronary arteries in patients with acute myocardial infarction - E. V. Aksonov; V. B. Golovenko; B. M. Gumenyuk; A. E. Gaponenko (Ukrainian Journal of Cardiovascular Surgery, 2019)
The work is devoted to the study of early and delayed postoperative angiographic results in patients with acute myocardial infarction (AMI). The survey included 626 patients with AMI without ST elevation, who underwent diagnostic and therapeutic interventional procedures for this pathology in the Angiographic Department of M.M. Amosov National Institute of Cardiovascular Surgery, National Academy of Medical Sciences of Ukraine. The average age of patients was 66.96±1.81 years; the average weight was 86.5±1.44 kg. The area of the left ventricular (LV) myocardial infarction in the calculation of the QRS index was an average of 20.4 ± 1.2%. 438 patients (69.97%) were with II FC heart failure by T. Killip. Primary transcutaneous transluminal balloon angioplasty (PTTBA) was performed in 332 patients who were examined at the early stages of AMI, and 294 patients underwent surgical stenting of the infarct-related artery (IRA) with single-stent implantation. The research has showed that primary stenting was the most effective method for recanalization compared with emergency or delayed IRA stenting, manifested in a more significant decrease in the area of primary AMI compared with emergency stenting and delayed intervention. In the group of patients who underwent IRA stenting, a correlation relationship was found between the development of residual coronary artery stenosis of more than 30% and baseline LV ejection fraction, baseline IRA blood flow and the ratio between the coronary artery diameter and the implantable stent diameter. In a statistically equal number of cases of clinical success, hospital mortality was higher upon IRA stenting by 3% compared with PTTBA. However, the delayed results of the three-month follow-up showed the benefits of stenting over PTTBA in terms of lower rates of myocardial infarction reocclusion (by 11.3%) and lower rates of delayed three-month lethality (by 6.7%).